Acúmulo de carbono no solo e potencial de aquecimento global influenciados pelo modo de aplicação de dejetos líquidos de suínos e inibidor de nitrificação - Santos, Daniela Batista dos (2016)
Studies about the effect of pig slurry (PS) injection in the soil and the use of nitrification inhibitors, such as dicyandiamide (DCD), have been focused on the dynamics of nitrogen in the soil-plant-atmosphere system. The aim of this work was to evaluate how the PS injection and the use of DCD can influence in total organic carbon accumulation in the soil (TOC) and the mitigation of global warming potential (GWP) due to the PS agricultural use as fertilizer in succession oats or wheat / corn under no-tillage. Two studies were conducted to field at the Federal University of Santa Maria, in experimental design of randomized blocks with four repetitions of the following treatments: PS applied on the soil surface (PSs), PSs + DCD, PS injected (PSi), PSi + DCD , mineral fertilizer (NPK) and control. The studies began in August and in December 2011 lasting 967 and 865 days on site 1 and 2, respectively. In the first place the PS application was manually, and the product Agrotain Plus®, which containing the DCD (81.0%), was applied at the rate of 10 kg ha-1. While in the second place exclusively PS injection was mechanized, whose grooves were spaced 0.35 m, in average depth 0.10 m and pure DCD was used in dose of 10 kg ha-1. In both places the DCD was mixed with PS at the moment of each application at cultures. Disturbed and undisturbed soil samples were collected at both sites in 2011 (initial condition) and in 2014, in the layers 0-0.05; 0.05-0.10; 0.10-0.20 and 0.20-0.30 m, and on site 2 the first layer was stratified into 0-0.025 and 0.025-0.05 m. We used the equivalent mass approach to determination of stocks TOC in the soil. During all the time from both experiments it was collected to greenhouse gas samples in order to quantify the cumulative emissions of nitrous oxide (N2O) and methane (CH4), and then convert them into CO2 equivalent and add them the rate of TOC accumulation in soil to estimate the net GWP (in area scale). To estimate the GWP in yield scale, it was divided the value of the net GWP by the average annual productivity of corn grain. The PS technique application and its combination with the DCD did not differ TOC accumulation in the soil neither the GWP. Regardless of the PS technique application and combination with DCD, the organic fertilization increases TOC accumulation in the soil and reduced the GWP compared to mineral fertilization. The PS injection associated with DCD increased the addition of C in the soil via biomass crops and COT accumulation in the soil in the layer from 0.00 to 0.30 m, compared to the absence of fertilization and NPK fertilization. Furthermore, when the PS are injected associated with the DCD it was observed at lower GWP in area scale than the mineral fertilizer, showing the environmental benefits of this first management. Negative values of the net GWP obtained in treatments with DCD indicate a positive potential effect of the nitrification inhibitor to mitigate emissions, this because the COT accumulation in the soil in these treatments was higher than the emissions of greenhouse gases. High GWP values in yield scale are observed in the control treatment, with no difference for this estimate, between organic and mineral fertilizers. It is noteworthy that there is a clear trend of associated injection to enable DCD environmental benefits through the reduction of greenhouse gas emissions, COT accumulation increment in soil and maintenance of grain yield.